Strategic electronic marketing : managing e-business - Kleindl, Brad Alan, 1955- (South-Western College, 2000)
Introduction to E-business. Understanding E-business technology. E-business communication. E-business distribution systems. E-business value strategies. The individual and the diffusion of innovations. Information collection and use...